Case Report: Invasive Fungal Infection and Daratumumab: A Case Series and Review of Literature - Farina, Francesca; Ferla, V.; Marktel, S.; Clerici, D.; Mastaglio, S.; Perini, T.; Oltolini, C.; Greco, R.; Aletti, F.; Assanelli, A.; Lupo-Stanghellini, M. T.; Bernardi, M.; et al. (Frontiers in Oncology, 2022)
Life expectancy of multiple myeloma (MM) patients has improved in last years due to the advent of anti-CD38 monoclonal antibodies in combination with immunomodulators and proteasome inhibitors. However, morbidity and mortality related to infections remain high and represent a major concern. This paper describes the “real life” risk of invasive fungal infections (IFI) in patients treated with daratumumab-based therapy and reviews the relevant literature. In a series of 75 patients we only observed three cases of fungal pneumonia. Unfortunately, the early signs and symptoms were not specific for fungal infection. Diagnostic imaging, microbiology and patient history, especially previous therapies, are critical in the decision to start antifungal treatment. Recognising the subgroup of MM patients with high risk of IFI can increase the rate of diagnosis, adequate treatment and MM-treatment recovery.